REAL TIME ASSESSMENT OF 500-KVA, 11/0.415 KV DISTRIBUTION TRANSFORMER SITUATED AT BELLS UNIVERSITY OF TECHNOLOGY, OTA, OGUN STATE USING FLUKE 435 SERIES II - ABRAHAM OLATIDE AMOLE; KAZIM IDOWU OKUSAGA; OLUFEMI OLANREWAJU ODEKUNLE; IKECHUKWU JOSEPH ODITA (Journal of Engineering Studies and Research)
Distribution transformer being major equipment in utility companies deserves to be routinely scrutinized for its performance with a view to ensure continuous supply of energy to end-users as well as to sustain improved revenue collection by the utility company. Presented in this paper is the real time assessment of 500-kVA, 11/0.415 kV distribution transformer situated at Bells University of Technology, Ota, Ogun State using power quality and energy analyzer equipment. The parameters measured on real time include phase to neutral voltage, phase to phase voltage, root mean square and peak current, frequency, active power, reactive and apparent power and line power factor. The assessment revealed wide variation of system voltages far from the standard, however, the line power factor and as well as frequency of operation was observed to be within the standard. Based on this analysis, several findings and appropriate recommendations were suggested to improve the supply of energy in the study area. It is hope that the findings of this research will be of immense benefit to distribution engineers at the Department of works in Bells University of Technology, Ota for field compliance.